2003
DOI: 10.1021/ef020113z
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Characterization of Inorganic and Mineral Matter in Coal:  A Critical Overview

Abstract: The present state of the methods commonly used for inorganic and mineral matter characterization in coal is described and summarized. The application of various separation procedures, macroscopic observations, reflected and transmitted optical microscopy, scanning and transmission electron microscopy, X-ray diffraction, differential thermal and thermogravimetric analyses, Mössbauer spectroscopy, infrared spectroscopy, and chemical analyses are briefly discussed. A short critical overview on the advantages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 180 publications
0
63
0
4
Order By: Relevance
“…4(a), it was observed that the major elemental compositions on the surface of raw coal were C and O, with minor Al and Ca attributed to clay minerals such as kaolinite, illite, and smectite, or carbonates such as calcite and siderite. 25,26 Aer the treatment of the alkali, parts of humic acids near the surface were removed, leaving a coarse surface (Fig. 3(b)).…”
Section: Ftir Analysis Of Humic Acidsmentioning
confidence: 99%
“…4(a), it was observed that the major elemental compositions on the surface of raw coal were C and O, with minor Al and Ca attributed to clay minerals such as kaolinite, illite, and smectite, or carbonates such as calcite and siderite. 25,26 Aer the treatment of the alkali, parts of humic acids near the surface were removed, leaving a coarse surface (Fig. 3(b)).…”
Section: Ftir Analysis Of Humic Acidsmentioning
confidence: 99%
“…Os constituintes inorgânicos do carvão incluem os minerais, tais como cristais, grãos e agregados de vários minerais e a matéria fluida (umidade e inclusões inorgânicas) associada com constituintes inorgânicos e orgânicos sólidos. 1 A caracterização físico-química do carvão apresenta vários desafios e a garantia da qualidade analítica dos dados é um fator muito importante em todas as etapas do ciclo de vida do carvão.…”
Section: Introductionunclassified
“…The measure we use for these elements is the reported ash concentration generated by high temperature ashing (Vassilev and Tascon, 2003) a process that converts the elements back to oxides. Some more volatile elements are lost during high temperature ashing (Vassilev and Tascon, 2003) but the major lithophile elements are preserved.…”
Section: Basis For Determining Dar From Coalmentioning
confidence: 99%
“…Some more volatile elements are lost during high temperature ashing (Vassilev and Tascon, 2003) but the major lithophile elements are preserved.…”
Section: Basis For Determining Dar From Coalmentioning
confidence: 99%